Preparation and properties of modified polyimide fibers/ethylene-propylene-diene monomer ablation resistant composites - "LIU Guo-qing, HU Jie, ZHANG Zheng, WANG Mei-fang, GAO Guo-wei, LIU Xue-tong, YANG Jing-ting, ZHANG Chun-mei, DU Ming-xin" (Hecheng xiangjiao gongye)
Surface modification of polyimide (PI) fiber was achieved with silane coupling agent (3-mercaptopropyl) trimethoxysilane (KH 590) as modifier, modified PI fiber/EPDM composites were prepared by thiol-ene radical addition reaction, and dispersion of fiber in the rubber matrix, interfacial adhesion between fiber and rubber matrix, mechanical properties and ablation resistance of the compo-sites were investigated by Fourier transform infrared spectroscopy, scanning electron microscopy, thermogravimetric analysis, etc. The results demonstrated that KH 590 was successfully grafted onto the PI fiber surface with a grafting ratio of 4.36%, impro-ving fiber dispersion in the matrix; compared to unmodified PI fiber/EPDM composite, the vulcanization rate of the modified PI fiber/EPDM composites decreased and the crosslinking degree increased; when the fiber addition amounts were all 5 phr (by mass), tensile strength, elongation at break, and tear strength of the modified PI fiber/EPDM composite were 37.9%, 97.0% and 31.0%, respectively, higher than those of the unmodified PI fiber/EPDM compo-site; when the fiber addition amount increased, the crosslinking degree of the composites increased, and both mechanical properties and ablation resistance improved.